Measurement of butterfly average resultant impulse per phase - Barbosa, Tiago M. (2019)
The aim of this study was to measure the average resultant impulse (ARI) per phase of the stroke cycle in butterfly and to analyse the variability of ARI according to the adopted breathing technique. The sample was composed of 6 male Portuguese swimmers at national and international level. 6 cameras were set, obtaining non coplanar images (2 "dual media" images included). The study comprised the kinematical analysis of stroke cycles of the butterfly stroke using the "Ariel Performance Analysis System" from Ariel Dynamics Inc. and a VCR at a frequency of 50 Hz. The ARI was calculated using the mean horizontal acceleration of the cenler of mass in each phase, the absolute duration of each phase and the body mass of the swimmer. Comparing the ARI according to the breathing technique adopted in each phase of the stroke cycle, we only observed significant differences in the outsweep. Comparing the intra-cyclic variations of the ARI in the different breathing techniques adopted, the arm's recovery when compared with the remained phases presented a significantly lower ARI.